What is the current status of care by neuro-otology specialists in Switzerland—A national survey - Zwergal, Andreas; Mantokoudis, Georgios; Heg, Dik; Kerkeni, Hassen; Diener, Suzie; Kalla, Roger; Korda, Athanasia; Candreia, Claudia; Welge-Lüssen, Antje; Tarnutzer, Alexander A. (Frontiers in Neurology, 2023)
Background Vertigo and dizziness are frequent presenting symptoms in the emergency department and in outpatient centers. While the majority of dizzy patients are evaluated by primary care physicians, specialists are often involved in the diagnostic workup. We aimed to gain more insights into the role of specialists in the care of dizzy patients. Materials and methods Board-certified neurologists and ear–nose–throat (ENT) physicians working in Switzerland were invited to participate in an online survey. Descriptive statistical analyses were performed, and prospectively defined hypotheses were assessed using correlation analyses. Results All 111 participating specialists (neurologists = 62; ENT specialists = 49) were familiar with testing for posterior canal benign paroxysmal positional vertigo (BPPV), and 66% regularly applied provocation maneuvers for suspected lateral canal BPPV. Reposition maneuvers for posterior (99%) and lateral (68%) canals were frequently performed. ENT physicians were familiar with lateral canal BPPV repositioning maneuvers significantly more often than neurologists (84 vs. 56%, p ≤ 0.012). Specialists strongly agreed that performing the head impulse test (86%) and looking for deficient eccentric gaze holding (82%) are important. Compared to neurologists, significantly fewer ENT physicians indicated ordering brain MRI in acutely dizzy patients (OR = 0.33 [0.16–0.067], p = 0.002) and physical therapy in patients with acute (50 vs. 20%, p = 0.005) or episodic/chronic dizziness (78 vs. 50%, p = 0.003). Conclusion We found substantial differences in the care of dizzy patients by neurologists and ENT physicians. This underlines the need for a standardized, guideline-oriented diagnostic workup and treatment across specialties. Dedicated training for performing lateral canal BPPV repositioning maneuvers should be prioritized for neurologists. Similarly, physical therapy should be considered more often by ENT physicians.